Ocean Acidification Has Impacted Coral Growth on the Great Barrier Reef. Issue 19 (25th September 2020) - Guo, Weifu; Bokade, Rohit; Cohen, Anne L.; Mollica, Nathaniel R.; Leung, Muriel; Brainard, Russell E.
Abstract: Ocean acidification (OA) reduces the concentration of seawater carbonate ions that stony corals need to produce their calcium carbonate skeletons and is considered a significant threat to the functional integrity of coral reef ecosystems. However, detection and attribution of OA impact on corals in nature are confounded by concurrent environmental changes, including ocean warming. Here we use a numerical model to isolate the effects of OA and temperature and show that OA alone has caused 13 ± 3% decline in the skeletal density of massive Porites corals on the Great Barrier Reef since 1950. This OA‐induced thinning of coral skeletons, also evident in Porites from the South China Sea but not in the central Pacific, reflects enhanced acidification of reef water relative to the surrounding open ocean. Our finding reinforces concerns that even corals that might survive multiple heatwaves are structurally weakened and increasingly vulnerable to the compounding effects of climate change Plain Language Summary: Measurable anthropogenic‐induced acidification of the oceans (OA) has occurred over the last four decades. But its impact on coral reef ecosystems, such as coral calcification, has yet to be unambiguously demonstrated. This problem with detection and attribution of OA impacts is due, in large part, to the fact that multiple co‐varying environmental and biological factors influence coral growth at the same time, and our inability to deconvolve them. Here, we use a numerical model of coral growth to isolate the contributions of ocean acidification to long coral growth timeseries generated on multiple Indo‐Pacific reefs over the 20th century. We show that ocean acidification has had a significant negative impact on skeletal growth of a keystone reef‐building genus across the Great Barrier Reef and in the South China Sea, where the rate of reef acidification outpaces that of the surrounding open ocean. Conversely, the OA‐induced thinning of coral skeletons observed on these reefs has not yet affected corals in the central Pacific, where the rates of reef acidification have been lower. Nevertheless, as ocean acidification accelerates over the next few decades, even these reefs will be affected, resulting in a measurable weakening of coral reef structures across the global tropics. Key Points: Numerical model of coral growth isolates the respective impacts of ocean acidification and ocean warming on coral growth Ocean acidification has caused ~13% decline in the skeletal density of massive Porites corals on the Great Barrier Reef since 1950 OA‐induced thinning of coral skeletons reflects enhanced acidification of reef water relative to the surrounding open ocean